As virtudes do trabalho artífice - Benites, Luis Henrique (2019)
This study aimed to investigate the artisanal mode of work in order to understand what the nature, limits and virtues are, inherent in this type of activity. The relevance of the problem studied stems from the perceptions of scholars who became involved with issues related to the increasing degradation of the life quality and well-being of workers in the contemporary times, driven by the technical efficiency and consequent establishment of instrumental ideology focused on the logic of progressive capital accumulation. To achieve the objective described above, an empirical research was carried out with artisan workers who use to perform their activities in the Curitiba / PR region. Specifically, five artisans were selected, chosen by geographical convenience, who perform their roles according to the assumptions of artisan labor, taking the control of the production process as a whole and, thus, autonomously exercising their condition to make decisions about their businesses. Methodologically, a descriptive-exploratory qualitative research was conducted, based on the in-depth interview method, combined with a participant observation section in the atelier of one of the artisans involved in this research, as well as the self-ethnography resulting from the author's own life experience, carrying out regular activities as an artisan baker. As a result, the following virtues of the artisanal mode of work were identified: (a) recognition, both the author's selfrecognition in his work, and the affective-emotional recognition, associated with the substantive recognition by the product, providing the craftsman with feelings such as pride, pleasure and job satisfaction; as well as honors of the craftsman for being able to create functional, personalized, exclusive products with characteristics considered positive for the customer and society, such as quality and durability, set by artisans as being superior to similar products produced through industrial processes; (b) autonomy, which gives the craftsman free will to make decisions about his business and (c) the learning community, established by the assumption of the craftsmanship, has the nature of continuous improvement. It was observed that they collaborate with each other, frequently sharing information and knowledge through digital media. In addition, it was found that the artisanal mode of work recognizes limits, both those of a physiological nature, inherent to humans, and certain technical aspects, linked to the physical and chemical characteristics of materials in place, as well as to factors determined by the nature, such as time and temperature, required by the nature to complete specific process at the artisanal production. Moreover, the findings about the nature of artisanal mode of work, corroborating the known literature, confirm that this is based on the possibility of the worker having physical contact with the material under transformation, performing his activities with his hands and mind. It is a working mode that allows the craftsman to be involved at all stages of the process, implying skills that are thoroughly practiced, which requires specific knowledge that is passed on from a master to his apprentice.